Modelling of Ion Transport in Solids with a General Bond Valence Based Force-Field - S. Adams; R.P. Rao (PPIKSN-BATAN, 2010)
Empirical bond length - bond valence relations provide insight into the link between structure of and ion transport in solid electrolytes. Building on our earlier systematic adjustment of bond valence (BV) parameters to the bond softness, here we discuss how the squared BV mismatch can be linked to the absolute energy scale and used as a general Morse-type interaction potential for analyzing low-energy pathways in ion conducting solid or mixed conductors either by an energy landscape approach or by molecular dynamics (MD) simulations. For a wide range of Lithium oxides we could thus model ion transport revealing significant differences to an earlier geometric approach. Our novel BV-based force-field has also been applied to investigate a range of mixed conductors, focusing on cathode materials for lithium ion battery (LIB) applications to promote a systematic design of LIB cathodes that combine high energy density with high power density. To demonstrate the versatility of the new BV-based force-field it is applied in exploring various strategies to enhance the power performance of safe low cost LIB materials (LiFePO4, LiVPO4F, LiFeSO4F, etc.).Received: 11 October 2010; Revised: 26 October 2010; Accepted: 28 October 2010